Exploring students' misconceptions using three-tier diagnostic test as the preliminary analysis for e-modules development on global warming and environmental pollution - Adika Muhammad Aziz; Mimin Nurjhani Kusumastuti; Taufik Rahman (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Misconceptions are challenges in education. Misconceptions can occur in science learning topics, one of which is the topic of global warming and environmental pollution. Misconception analysis is conducted as one of the diagnostic tests to analyze misconceptions in students and as an early stage of developing teaching materials. This study aims to provide an overview of student misconceptions that occur in the material of global warming and environmental pollution. This research uses a quantitative descriptive method with the data from multiple-choice answers using the three-tier diagnostic test misconception question and the results were grouped using a three-level misconception categorization. The sample in this study amounted to 96 students, with global warming and environmental pollution as the focused topics. The results showed that 57.9% of students' answers were misconceptions, 30.1% of students' answers were scientific knowledge, 2.7% of students' answers were lucky guesses, and 9.3% of students' answers were lack of knowledge. The larger number of misconception categories indicates that students still do not correctly understand the concepts of global warming and environmental pollution. Students who are included in the misconception category appear to have believed in the wrong knowledge about global warming and environmental pollution. This belief in erroneous knowledge is a challenge for educators to correct students' misconceptions. Thus, the results of this misconception analysis can be an important asset for the development of e-modules to reduce the level of students' global warming and environmental pollution misconceptions.Abstrak. Miskonsepsi merupakan tantangan dalam pendidika. Miskonsepsi dapat terjadi pada topik pembelajaran sains, salah satunya adalah topik pemanasan global dan pencemaran lingkungan Analisis miskonsepsi dilakukan sebagai salah satu tes diagnostik untuk menganalisis miskonsepsi pada siswa dan sebagai tahapan awal pengembangan bahan ajar. Tujuan dari penelitian ini adalah untuk memberikan gambaran mengenai miskonsepsi siswa yang terjadi pada materi pemanasan global dan pencemaran lingkungan. Penelitian ini menggunakan metode deskriptif kuantitatif dengan data yang digunakan adalah hasil jawaban pilihan ganda menggunakan intrumen tes diagnostik tiga-tingkatan dan hasilnya dikelompokkan menggunakan kategorisasi tiga-tingkatan Sampel pada penelitian ini berjumlah 96 siswa, dengan materi pemanasan global dan pemcemaran lingkungan sebagai topik yang difokuskan. Hasil penelitian ini menunjukkan bahwa sebanyak 57,9% jawaban siswa mengalami miskonsepsi, 30,1% jawaban siswa merupakan scientific knowledge, 2,7% jawaban siswa merupakan lucky guess, dan 9,3% jawaban siswa merupakan lack of knowlegde. Jumlah kategori miskonsepsi yang lebih banyak menunjukkan bahwa siswa masih belum memahami dengan benar konsep-konsep pada materi pemanasan global dan pencemaran lingkungan. Siswa yang termasuk dalam kategori miskonsepsi rupanya telah meyakini pengetahuan yang salah terhadap pemanasan global dan pencemaran lingkungan. Keyakinan terhadap pengetahuan yang keliru ini merupakan tantangan bagi pendidik untuk meluruskan kesalahpahaman siswa. Dengan demikian, hasil dari analisis miskonsepsi ini dapat menjadi modal penting bagi pengembangan e-modul guna menurunkan tingkat miskonsepsi pemanasan global dan pencemaran lingkungan siswa.